Simulation of loess gully evolution based on geographic cellular automata. Issue 3 (27th November 2021) - Luo, Lanhua; Ma, Jin; Li, Fayuan; Jiao, Haoyang; Strobl, Josef; Zhu, A‐xing; Dai, Ziyang; Liu, Shuanglin
Abstract: Gully development is an important topic in the evolution of modern geomorphology. The study of the development process of gullies is key to understanding the genesis, mechanism and spatial differentiation of loess geomorphology. This study explored the mechanism of the development process of gullies whilst taking into account the erosion characteristics of the gully head area, gully slope area and gully bed area. Based on geographic cellular automata (Geo‐CA), the transition rules were interacted with the fundamental hydraulic principles for gully evolution simulation. Different sediment transfer rules apply to the gully slope area and gully bed area. A simulation model of the loess gully evolution was constructed and implemented based on the loess simulation small watershed. The superior performance of the model was demonstrated by the accuracy evaluation of the model structure and the comparative analysis of the modelling results. Moreover, the model was validated by natural watershed data, and the analytical results indicated the feasibility of the model. Abstract : Taking gully erosion process as the theoretical basis, combined with the geographical cellular automata (Geo‐CA), based on the simulated small watershed data, the transition rules based on dynamic formula are set, and the loess gully development and evolution model is constructed. The model is applied to the natural watershed to demonstrate the effectiveness and simulation accuracy of the model.